Effect of Human Chorionic Gonadotropin Injection Before Frozen Embryo Transfer on Pregnancy Outcomes in Endometriosis-Associated Infertility - Du, Yanbo; Yan, Lei; Sun, Mei; Sheng, Yan; Li, Xiufang; Feng, Zhenhua; Tang, Rong (Frontiers in Medicine, 2020)
Purpose: To investigate the effect of human chorionic gonadotropin(hCG) in hormone replacement regime for frozen thawed embryo transfer in women with endometriosis. Methods: We performeda retrospective, database-search, cohort study and included data on endometriosis patients who underwent frozen embryo transfer between January 1, 2009 and August 31, 2018. According to the protocols for frozen embryo transfer cycle, the patients were divided into two groups: control group (n=296) and hCG group (n=355). Clinical pregnancy rate, live birth rate, early abortion rate, late abortion rate, and ectopic pregnancy rate were compared between the two groups. Results: There was a significant increase in clinical pregnancy rate in the hCG group (57.7%% vs.49%, p=0.027) compared to the control group. The live birth rate in the hCG group (45.6% vs. 38.5%,p=0.080) was also elevated, but this difference was not statistically significant. Conclusion: hCG administration in hormone replacement regime for frozen embryo transfer increases the pregnancy rate in women with endometriosis.